Karakterisasi Material Polimer PVDF dengan Polarisasi Permukaan - Nugraha, Aditya; Ardin, Masri Bin; Rezani, Rivandra (Jurnal Rekayasa Mesin, 2017)
Polivinylidene fluoride (PVDF) is one type of polymer. PVDF is commonly used as a force, heat and strain sensors due to its piezoelectric properties. However, it needs a special process to create the piezoelectric properties of PDVF. One of the special process to create the piezoelectric properties is surface polarization of PVDF. Two electrodes were placed on the surface of PVDF and a high-voltage DC electricity was used for polarization process. In this study, Piezoresponse Force Microscopy (PFM) and Fourier Transformed Infrared (FTIR) was used to determine the results of the surface polarization. The results showed that PVDF with lateral polarization has a more orderly domain direction and a higher Î² phase compared to unpolarized PVDF. In addition, the quality decreased with increasing the electrode distance in the lateral polarization.